A Survey of Data Mining Techniques for Smart Museum Applications - Shinta Puspasari; Ermatita Ermatita (JUITA : Jurnal Informatika, 2021)
This research aims to find out what data mining techniques are effectively implemented in museums and what application trends are currently being used to improve museum performance towards modern museums based on intelligent system technology. The review was carried out on a number of articles found in journals and proceedings in the 2004-2020 period. It is found that the majority of data mining techniques are implemented in museum virtual guide applications, recommender systems, collection clustering and classification system, and   visitor behaviour prediction application. Data classification, clustering, and prediction technique commonly used for museum application.  Collections with historical and artistic value  contain a lot of knowledge making data mining an important technique to be included in various applications in museums so that they can have an impact on the achievement of museum goals not only in the fields of education and culture but also economics and business.